Answer:
M=-3
Step-by-step explanation:
Slope:
y2-y1/x2-x1
-3-3/1+1=6/-2=-3
Answer:
x=40/33
Step-by-step explanation:
Let's solve your equation step-by-step.
25(4x−3)−2x=45−x
Step 1: Simplify both sides of the equation.
25(4x−3)−2x=45−x
(25)(4x)+(25)(−3)+−2x=45+−x(Distribute)
100x+−75+−2x=45+−x
(100x+−2x)+(−75)=−x+45(Combine Like Terms)
98x+−75=−x+45
98x−75=−x+45
Step 2: Add x to both sides.
98x−75+x=−x+45+x
99x−75=45
Step 3: Add 75 to both sides.
99x−75+75=45+75
99x=120
Step 4: Divide both sides by 99.
99x
99
=
120
99
x=
40
33
Answer:
x=40/33
Having the angle in radians and the diameter of the circle we can easily calculate the length using the following expression
Length = angle(radians)*diameter/2
With this expression we can easily deduce the perimeter of a circle (length of the full arc)
Length = Perimeter = 2*pi*r
There is only one operation involved in this process
Answer:
Choice b.
.
Step-by-step explanation:
The highest power of the variable
in this polynomial is
. In other words, this polynomial is quadratic.
It is thus possible to apply the quadratic formula to find the "roots" of this polynomial. (A root of a polynomial is a value of the variable that would set the polynomial to
.)
After finding these roots, it would be possible to factorize this polynomial using the Factor Theorem.
Apply the quadratic formula to find the two roots that would set this quadratic polynomial to
. The discriminant of this polynomial is
.
.
Similarly:
.
By the Factor Theorem, if
is a root of a polynomial, then
would be a factor of that polynomial. Note the minus sign between
and
.
- The root
corresponds to the factor
, which simplifies to
. - The root
corresponds to the factor
, which simplifies to
.
Verify that
indeed expands to the original polynomial:
.
(yX3)+1 because product means multipy